Homeless in Maine: Who Is? Who Might Be Tomorrow? What Do We Do About It? - Guild, Suzanne (Maine Policy Review, 1999)
The December 1998 denial by the U.S. Department of Housing and Urban Development to fund Maine’s applications for homeless assistance catapulted the needs of this vulnerable population to top priority status. As Suzanne Guild notes, Maine’s homeless population is comprised of two groups: those who are homeless for the first time and who, after a brief stay at a shelter, will regain stable housing, and those who cycle in and out of the state’s shelters on a more or less regular basis. Both groups tend to be young and undereducated; more than half are male; and many report problems with alcohol and/or drug dependence. Still another group comprises Maine’s “near-homeless” population. More of these individuals are women, many with children; they are also young and undereducated. In this article, Suzanne Guild carefully describes the characteristics of these groups and asks, “So what do we do?” She offers four prescriptions for assistance: commit more funds to the Shelter Operating Subsidy program, streamline the General Assistance process, recognize that homelessness is not simply a housing problem, and talk about homelessness in a kinder and gentler fashion.
Keywords: Maine; homelessness; homeless shelters